An Analysis of Common Weaknesses in the Results of the Language Proficiency Test among Students of the Arabic Language Education Department at Makassar State University - Noor Afifah Bashiri; Ruhul Kudus (Al-Muyassar: Journal of Arabic Education, 2025)
This study aims to identify common weaknesses faced by university students in the Test of Arabic as a Foreign Language exam. The main focus is on Arabic comprehension skills in various aspects such as reading, writing, speaking, and listening. This study used descriptive analysis method with qualitative approach. Data were collected through students' TOAFL exam results, which were then analyzed to identify patterns of common weaknesses. This research also refers to various literatures and previous studies to strengthen the findings. The results showed that students experienced the greatest difficulties in the aspects of reading comprehension and proper vocabulary usage. Many students were unable to comprehend the text well and were often incorrect in their use of words. In addition, it was also found that students' writing and speaking skills still need to be improved, especially in terms of sentence structure and grammar. This study suggests the need for more effective teaching strategies to improve students' Arabic language skills. The recommendations include increased vocabulary practice, the use of more diverse texts in teaching, and an emphasis on a deeper understanding of grammar. Thus, it is expected that students' TOAFL exam results can improve significantly.Â Keywords: analysis, common weaknesses, TOAFL exam